2008
DOI: 10.1007/s10802-008-9264-2
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Adolescent Depressive Symptoms: The Role of Parental Attributions

Abstract: This study examined whether negative parental attributions for adolescent behaviour mediate the association between parental and adolescent depressive symptoms, and whether this relationship is moderated by adolescent gender. Mothers and fathers and 124 adolescents (76 girls and 48 boys; ages 14 to 18) participated. Adolescents were primarily Caucasian, and varied in the level of depressive symptoms (with 27% of the sample meeting diagnostic criteria for a current unipolar depressive disorder). Parents and ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 71 publications
4
47
5
Order By: Relevance
“…However, only father negative attributions significantly predicted behavior problems above and beyond ADHD status and mother attributions at Time 1, and continued to predict subsequent behavior problems at Time 2 with initial levels of behavior problems also controlled. The relations of negative parental attributions to boys' behavior problems are not surprising, and replicate previous research across range of child behavior problems (e.g., Chen et al, 2009;Markel & Wiener, 2012;Werner, 2012). However, compared to the previous literature, the strength of the current study is its equal focus on fathers and mothers, and our results support the importance of father attributions, at least for sons.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, only father negative attributions significantly predicted behavior problems above and beyond ADHD status and mother attributions at Time 1, and continued to predict subsequent behavior problems at Time 2 with initial levels of behavior problems also controlled. The relations of negative parental attributions to boys' behavior problems are not surprising, and replicate previous research across range of child behavior problems (e.g., Chen et al, 2009;Markel & Wiener, 2012;Werner, 2012). However, compared to the previous literature, the strength of the current study is its equal focus on fathers and mothers, and our results support the importance of father attributions, at least for sons.…”
Section: Discussionsupporting
confidence: 88%
“…Compared to mothers, fathers make unique contributions to aspects of child development such as social skills (Kaiser, McBurnett, & Pfiffner, 2011), empathy (Pleck, 1997), and adjustment in adolescence (Leidy et al, 2011). In addition, mother and father attributions for child behavior may not only be different (e.g., Chen, Seipp, & Johnston, 2008;Lansford et al, 2011) but also may be differentially associated with child outcomes (Chen, Johnston, Sheeber, & Leve, 2009;Markel & Wiener, 2012;Werner, 2012). Differential relations with mother and father attributions have been found for both internalizing and externalizing child problems.…”
Section: Mother and Father Attributionsmentioning
confidence: 99%
“…Domestic violence 20 and stressful life events 21 were revealed in studies to be associated with depression in adolescents. Similar studies revealed 22 parental depressive symptom and parental negative attribution lead to adolescent depression.…”
Section: Discussionsupporting
confidence: 54%
“…Mothers who reported high depressive symptoms blamed their daughters more while they gave less credits to positive behaviors, whereas high depressive symptoms did not influence fathers' behavior toward their daughters (Chen, Johnston, & Sheeber, 2009). These differences may relate to the adolescent's gender.…”
Section: Discussionmentioning
confidence: 93%